Consumers’ loyalty toward Islamic banking system: does halal brand awareness matter? - Maulan, Suharni (IIUM Press, 2016)
In a competitive market structure, brand awareness helps to create a basis of trust and acceptance. Brand awareness is the first step to creating brand equity, an asset that provides companies with sustainable competitive advantages. However, in the Islamic banking context, the majority of consumers are still unable to distinguish between Islamic and conventional banks despite their awareness of the Islamic banking existence. This concern is critical to be addressed particularly in a dual banking environment such as in Malaysia, where consumers have choices between the Islamic and the conventional banking systems. Accordingly, this paper aims at investigating the influence of hạlāl brand awareness on consumer loyalty toward the Islamic banking system. The model also includes brand loyalty as it is the core asset of brand equity. Using survey method, data of 454 respondents have been analyzed using PLS-SEM. The findings reveal that hạlāl brand awareness shows greater influence on consumer loyalty toward the Islamic banking system than brand loyalty. Thus, Islamic bank managers must operationalize effective marketing communication strategies by promoting the Islamic banking products with simplicity to facilitate greater consumer understanding. This is not merely for enhancing organizational competitiveness, but more importantly is to ensure long term Islamic banking industry resilience.